(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Acute pancreatitis (AP) is defined as inflammatory process due to auto-digestion of the gland by pancreatic digestive enzymes, leading to impairment of function or any morphologic changes. Objective: The study provides comprehensive insights into the demographic, clinical, and biochemical characteristics of acute pancreatitis patients. Methods: This Prospective observational study was conducted among patients attending OPD and IPD of General Medicine department of KBN Teaching & General Hospital Kalaburagi. Period of Study was 18 months (1st march 2023 to 30th September 2024). Result: The study highlights the diverse presentations and severity of acute pancreatitis, emphasizing the prognostic value of BISAP and CT severity scores. While gender was not a determining factor in disease severity, age and specific biochemical markers significantly influenced patient outcomes. These findings underscore the need for early detection and targeted management strategies to improve prognosis. Conclusion: The study identified BISAP as reliable predictor of disease prognosis. Higher BISAP score is strongly associated with increased mortality (P<0.001), emphasizing their role in early risk stratification.